English Material Needs of Accounting Students: An English for Specific Purposes Approach - Arif Nugroho (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
AbstractThe appropriateness of teaching materials is one of the essential components in gaining the maximum input of knowledge to achieve the success of a language learning. In terms of teaching English for specific purposes, the contextualized material is a prerequisite to encourage the learners’ productivity in using the language. Therefore, the present study sheds light on English teaching material needs of accounting students at IAIN Surakarta and the challenges that accounting students face to fulfil the needs. Descriptive qualitative was employed in this study by administering Focus Group Discussion (FGD) and web-based survey to the first-year accounting students who had finished English for Specific Purposes course as the participants. Semi-structured interview was also conducted with the English lecturers and the head of accounting department to enrich the data. The data were analysed by transcribing the results of FGD and semi-structured interview and describing the questionnaire results as data triangulation. The findings of this study showed that contextual English teaching materials are strongly needed by accounting students to enhance their language production. Moreover, there are some insights from the participants related to the ideal teaching materials for accounting students. These findings offer practical insights in designing a representative teaching material for accounting students to equip them with outstanding language skills in accounting field.